Analysis of Levels of Metacognition Ability in Solving Problem-Based Problems in Science Learning Based on Gender Differences - Faninda Novika Pertiwi; Salwa Nusaibah Nusaibah (Pendidikan IPA, FMIPA, UNP, 2023)
Metacognition has a role in regulating and monitoring one's cognitive processes in thinking and learning. Students can solve problems well when applying metacognition strategies. Each student has different abilities in understanding learning material. Where male and female students have different ways of thinking, as well as solving a problem. This study aims to describe the level of metacognitive abilities of male and female students in solving problem-based questions in science learning. This type of research is descriptive qualitative research. This research was conducted at MTs Al-Islam by taking three male and three female subjects. The selection of subjects is based on the value of student learning outcomes which are limited by a certain standard deviation. This study used written tests and interviews as instruments for data collection. The results are 1) Male students in the high category are at the strategic use level, male students in the medium category are at the aware use level and male students in the low category are at the tacit use level. 2) Female students in the high category are at the level of reflective use, female students in the middle category are at the level of strategic use and female students in the low category are at the level of aware use.